Design and performance of frames with intentionally eccentric braces - González Ureña, Andrés (2020)
Concentrically Braced Frames (CBFs) with Hollow Structural Sections (HSSs) as the bracing members present significant shortcomings that pose limits to their convenience. Due to their inherently stiff nature, CBFs are usually constrained to low fundamental periods of vibration and, thus, high acceleration and force demands, which, in conjunction with the intrinsic overstrength that derives from the compression resistance controlling the dimensioning of the bracing members, results in high design forces for the capacity-protected components of the structure and its foundations. Furthermore, their ductility and energy dissipation capacity are hindered by the susceptibility of HSSs to low-cycle fatigue induced premature fracturing at the plastic hinge region after the onset of local buckling. To address these shortcomings of Conventional Concentric Braces (CCBs), researchers from Japan recently proposed the use of Braces with Intentional Eccentricity (BIEs). Being subject to both flexural and axial deformations under axial loading, BIEs are inherently less stiff than CCBs. Moreover, their axial stiffness can be adjusted by varying the eccentricity to obtain the desired frame response. Also, initiation of local buckling occurs at larger axial displacements because the strain demand is more evenly distributed over the brace length. However, BIEs are not well suited for standard force-based design procedures given that the force they develop varies continuously with their axial deformation, and that they attain their maximum capacity at large deformation values that depend on the eccentricity. For this reason, the use of BIEs compels the use of an alternative design approach that handles explicitly their particular response to loading. This article presents a Direct Displacement-Based Design (DDBD) procedure for the seismic design of Frames with Intentionally Eccentric Braces (FIEBs). The proposed procedure includes provisions aiming to control the performance of the structure when subjected to design level earthquakes and to minimize its damage under frequent earthquakes. The method is applied to prototype buildings of 4, 8 and 12 storeys, with square HSS bracing members, and considering two levels of target drift ratio. The structures are designed for a region of high seismic hazard and for a region of moderate seismic hazard, both within Canada. The performance of the so designed buildings is then evaluated through Non-Linear Response-History Analysis (NLRHA). The results show that the seismic performance of FIEBs is satisfactory and on par with the performance objectives incorporated in the procedure and those of the National Building Code of Canada. Furthermore, the resulting tonnage of the FIEB buildings is compared to that of traditional Moderately Ductile and Limited Ductility CBFs designed for identical conditions, showing that FIEBs may constitute an economically advantageous alternative to conventional CBFs, specially in the case of moderately tall buildings located in regions of high seismic hazard.